2019
DOI: 10.1021/jacs.9b01056
|View full text |Cite
|
Sign up to set email alerts
|

Green-Light-Triggered Phase Transition of Azobenzene Derivatives toward Reversible Adhesives

Abstract: Studies on the azobenzene derivative based phase transitions mostly rely on photoisomerization, which require a long time to spontaneously revert back. Here we show a photothermal-driven solid-to-liquid transition and fast reversion of azobenzene derivatives. Owing to the aggregation of suitably substituted azobenzenes, solid-to-liquid transitions can be induced by photothermal effects under irradiation with green light. The liquid-state azobenzene derivatives spontaneously solidify again within 2 min due to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 32 publications
2
126
1
Order By: Relevance
“…Moreover, we also measured the fluorescence lifetimes of above six samples. Using the absolute quantum yield and fluorescence lifetime, we calculated the radiative constant rate ( k r ) and nonradiative constant rate ( k nr ) of above six samples . We found that the k nr / k r ratio of the fluorophore Cypate in 1‐NPs (i.e., simultaneous intra‐ and intermolecular quenching, k nr / k r = 997.8) is much larger than that in either 1‐Dimer (i.e., intramolecular quenching, k nr / k r = 15.7) or 1‐Fmoc‐NPs (i.e., intermolecular quenching, k nr / k r = 499.3) (Table.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also measured the fluorescence lifetimes of above six samples. Using the absolute quantum yield and fluorescence lifetime, we calculated the radiative constant rate ( k r ) and nonradiative constant rate ( k nr ) of above six samples . We found that the k nr / k r ratio of the fluorophore Cypate in 1‐NPs (i.e., simultaneous intra‐ and intermolecular quenching, k nr / k r = 997.8) is much larger than that in either 1‐Dimer (i.e., intramolecular quenching, k nr / k r = 15.7) or 1‐Fmoc‐NPs (i.e., intermolecular quenching, k nr / k r = 499.3) (Table.…”
Section: Resultsmentioning
confidence: 99%
“…Second, Yin'sgroup reported the phase transition of azobenzene-containing compounds by photothermal effect based on the adsorption of visible light. [25] It avoidedt he drawbacks of UV light irradiation, such as low penetration and light-induced damageso fm aterials. Visible-light-controlled solid-to-liquid transitions are necessary, especially for azopolymers.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of typical examples with adhesion strength over 1 MPa on diverse substrates is shown in Table 1. 23,53,[55][56][57][58][59][60][61][62] Typical molecular weights of these monomers are below 2,000 g/mol, with a minimum of 186 g/mol, whereas the binding strength values are comparable with those of commercial superglues, allowing SSSA to be worth investigated further as macroscopic adhesion materials.…”
Section: High-strength Supramolecular Adhesivesmentioning
confidence: 99%